Bilateral parasternal and rectus sheath blocks reduce pain post-cardiac surgery: a pilot trial - Huang, Yangsi; Ouyang, Chengdi; He, Fang; Zhong, Yu; Liu, Guofeng; Lu, Yizhi; Chen, Yanhua (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to investigate the effects of ultrasound-guided bilateral parasternal block (PSB) combined with rectus sheath block (RSB) on postoperative recovery quality in patients undergoing median sternotomy for cardiac surgery.MethodsEighty patients were randomly assigned to either the intervention group (receiving PSB + RSB, n = 40) or the control group (not receiving PSB + RSB, n = 40). The primary outcome was opioid consumption within the first 24 h postoperatively. Secondary outcomes included Visual Analog Scale (VAS) pain scores and various surgery and recovery-related parameters.ResultsThe intervention group showed significantly reduced opioid consumption in the first 24 h postoperatively compared to the control group (P < 0.05), though no significant difference was observed at 48 h postoperatively. VAS pain scores at extubation and at 12, 24, and 48 h post-extubation were significantly lower in the intervention group (P < 0.05). The intervention group also demonstrated superior Quality of Recovery-15 (QoR-15) scores at all observed time points compared to the control group (P < 0.05), with no block-related adverse events. There were no significant differences in surgical and recovery-related parameters between the groups.ConclusionUltrasound-guided bilateral PSB combined with RSB effectively enhances postoperative analgesia and the quality of recovery in patients undergoing median sternotomy for cardiac surgery. The application of ultrasound-guided bilateral parasternal block combined with rectus sheath block in median sternotomy cardiac surgery offers a new pain management strategy that is both safe and highly effective. This approach reduces postoperative analgesic requirements and improves recovery quality for cardiac surgery patients.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=180456, China Clinical Trial Registry (ChiCTR2200064733).